Activation of the RAS/B‐RAF‐MEK‐ERK pathway in satellite glial cells contributes to substance p‐mediated orofacial pain. (5th December 2019) - Zhang, Yan‐yan; Song, Ning; Liu, Fei; Lin, Jiu; Liu, Meng‐ke; Huang, Chao‐lan; Liao, Da‐qing; Zhou, Cheng; Wang, Hang; Shen, Jie‐fei
Abstract: The cross talk between trigeminal ganglion (TG) neurons and satellite glial cells (SGCs) is crucial for the regulation of inflammatory orofacial pain. Substance P (SP) plays an important role by activating neurokinin (NK)‐I receptors in this cross talk. The activation of extracellular signal‐regulated kinase (ERK) 1/2, protein kinase A (PKA) and protein kinase C (PKC) in neurons and SGCs of peripheral ganglions by peripheral inflammation is associated with inflammatory hypersensitivity. This study tested the hypothesis that SP evoked SP‐NK‐I receptor positive feedback via the Renin–Angiotensin System/B‐Protein Kinase A‐Rapidly Accelerates Fibrosarcoma‐MEK‐Extracellular Signal‐Regulated Kinase (RAS/PKA‐RAF‐MEK‐ERK) pathway, which is involved in pain hypersensitivity. Inflammatory models were induced in vivo by injecting Complete Freund's adjuvant (CFA) into the whisker pad of rats. SP was administrated to SGCs in vitro for investigating, whether SP regulates the expression of NK‐I receptor in the SGC nucleus. The effects of RAS‐RAF‐MEK, PKA and PKC pathways in this process were measured by co‐incubating SGCs with respective Raf, PKA, PKC and MEK inhibitors in vitro and by pre‐injecting these inhibitors into the TG in vivo. SP significantly upregulated NK‐I receptor, p‐ERK1/2, Ras, B‐Raf, PKA and PKC in SGCs under inflammatory conditions. In addition, L703, 606 (NK‐I receptor antagonist), U0126 (MEK inhibitor), Sorafenib (Raf inhibitor) and H892HCL (PKA inhibitor) but not chelerythrine chloride (PKC inhibitor) significantly decreased NK‐I mRNA and protein levels induced by SP. The allodynia‐related behavior evoked by CFA was inhibited by pre‐injection of L703, 606, U0126, Sorafenib and H892HCL into the TG. Overall, SP upregulates NK‐I receptor in TG SGCs via PKA/RAS‐RAF‐MEK‐ERK pathway activation, contributing to a positive feedback of SP‐NK‐I receptor in inflammatory orofacial pain. Abstract : SP evoked SP‐NK‐I receptor positive feedback via the Renin–Angiotensin System/B‐Protein Kinase A‐Rapidly Accelerates Fibrosarcoma‐MEK‐Extracellular Signal‐Regulated Kinase (RAS/PKA‐RAF‐MEK‐ERK) pathway, which is involved in pain hypersensitivity. SP upregulated NK‐I receptor, p‐ERK1/2, Ras, B‐Raf, PKA and PKC in SGCs under inflammatory conditions. L703, 606 (NK‐I receptor antagonist), U0126 (MEK inhibitor), Sorafenib (Raf inhibitor) and H892HCL (PKA inhibitor) decreased NK‐I induced by SP. CFA induced inflammation pain in rats, and SP involved the regulation of this inflammatory pain. The allodynia‐related behavior evoked by CFA was inhibited by pre‐injection of L703, 606, U0126, Sorafenib and H892HCL into the TG. SP upregulates NK‐I receptor in TG SGCs via PKA/RAS‐RAF‐MEK‐ERK pathway activation, contributing to a positive feedback of SP‐NK‐I receptor in inflammatory orofacial pain.